Use of probiotic lactobacilli in the treatment of vaginal infections: In vitro and in vivo investigations - Liu, Peng; Lu, Yune; Li, Rongguo; Chen, Xiaodi (Frontiers in Cellular and Infection Microbiology, 2023)
The vaginal microbiome is a distinct component of the human microbiome that is colonized by a wide variety of microorganisms. Lactobacilli are the most frequently identified microorganisms in the healthy human vagina. These Gram-positive bacilli can acidify the vaginal microenvironment, inhibit the proliferation of other pathogenic microorganisms, and promote the maintenance of a eubiotic vaginal microbiome. However, a vaginal flora with a reduced proportion or abundance of lactobacilli is associated with various vaginal infections that have been linked to serious health consequences such as infertility, preterm birth, pelvic inflammatory disease, premature rupture of membranes, and miscarriage. Due to their “Generally Recognized as Safe” classification and critical role in vaginal health, probiotic lactobacilli have been widely used as an alternative or adjunct to traditional antibiotic therapy for the treatment of vaginal infections and restoration of the vaginal microbiome. This review focuses on the significant role of probiotic lactobacilli in the vaginal microenvironment and discusses the use of probiotic lactobacilli in the treatment of female vaginal infections in vitro and in vivo.